Validitas E-Book Berbasis Flip PDF Corporate pada Pembelajaran Pendidikan Pancasila di Kelas V Sekolah Dasar - Putri, Nurul Ikhsani; Adrias, Adrias; Putera, Rafhi Febryan; Mansurdin, Mansurdin; Ladiva, Hasmai Bungsu (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the validity of the corporate flip pdf-based e-book in the Civic Education learning for Grade V of Elementary School. The type of research method used in this study is R&D (Research and Development) research. The development model that will be used in this research is the ADDIE model. The data collection techniques used are observation, interviews, and questionnaires. The collected data is analyzed descriptively. The analysis results show that the development process received a percentage rating of 97.5% from content expert validators, 100% from language expert validators, and 95.83% from media expert validators. From the average score calculation of the three validators, a final validation score of 97.77% was obtained, categorized as 'Very Valid'. This result illustrates that the developed e-book is valid and can be used in the classroom learning process.